Engineering blood vessels through micropatterned co-culture of vascular endothelial and smooth muscle cells on bilayered electrospun fibrous mats with pDNA inoculation. (1st January 2015) - Liu, Yaowen; Lu, Jinfu; Li, Huinan; Wei, Jiaojun; Li, Xiaohong
Graphical abstract: Abstract: Although engineered blood vessels have seen important advances during recent years, proper mechanical strength and vasoactivity remain unsolved problems. In the current study, micropatterned fibrous mats were created to load smooth muscle cells (SMC), and a co-culture with endothelial cells (EC) was established through overlaying on an EC-loaded flat fibrous mat to mimic the layered structure of a blood vessel. A preferential distribution of SMC was determined in the patterned regions throughout the fibrous scaffolds, and aligned fibers in the patterned regions provided topological cues to guide the orientation of SMC with intense actin filaments and extracellular matrix (ECM) production in a circumferential direction. Plasmid DNA encoding basic fibroblast growth factors and vascular endothelial growth factor were integrated into electrospun fibers as biological cues to promote SMC infiltration into fibrous mats, and the viability and ECM production of both EC and SMC. The layered fibrous mats with loaded EC and SMC were wrapped into a cylinder, and engineered vessels were obtained with compact EC and SMC layers after co-culture for 3 months. Randomly oriented ECM productions of EC formed a continuous endothelium covering the entire lumenal surface, and a high alignment of ECM was shown in the circumferential direction of SMC layers. The tensile strength, strain at failure and suture retention strength were higher than those of the human femoral artery, and the burst pressure and radial compliance were in the same range as the human saphenous vein, indicating potential as blood vessel substitutes for transplantation in vivo. Thus, the establishment of topographical cues and biochemical signals in fibrous scaffolds demonstrates advantages in modulating cellular behavior and organization found in complex multicellular tissues.